A sodium ion battery layered oxide positive electrode material based on surface reconstruction and its preparation method and application
By quenching the sodium ion battery positive electrode material in aqueous molybdate solution, the surface reconstruction layer of disordered rock salt/layered heterostructure is formed, which solves the problem of structural instability of the positive electrode material under high voltage, improves the specific capacity and cyclic performance of the material, and simplifies the preparation process, which is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411947689.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing sodium ion battery layered oxide positive electrode materials are unstable at high voltages, resulting in short cycle life and low energy density, and complex preparation process and not suitable for large-scale industrial production.
Using a surface reconstruction-based method, the positive electrode material is quenched in the aqueous molybdate solution to form a surface reconstruction layer of disordered rock salt/layered heterostructure to improve the interface stability of the material under high pressure.
It significantly improves the specific capacity and circulation performance of the positive electrode material, extends the charge and discharge cycle life, reduces the harmful effects of the electrode-electrolyte interface reaction, and is suitable for large-scale industrial production.
Smart Images

Figure CN119381439B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a sodium ion battery layered oxide positive electrode material based on surface reconstruction, and a preparation method and application thereof. Background Art
[0002] With the growing global energy demand and the rapid development of renewable energy, the problem of insufficient lithium resources and uneven global distribution has become increasingly prominent. However, sodium resources are abundant, widely distributed and inexpensive. Sodium-ion batteries (SIBs) have great commercial value and application potential in the fields of electric vehicles and large-scale energy storage. However, the commercialization process of SIBs is constrained by their relatively low energy density and insufficient cycle life. The main reason is that sodium has a higher standard electrode potential than lithium (the chemical potential of the sodium ion couple is ~0.3V lower than that of the lithium ion couple) and a larger mass / volume. Therefore, improving the output voltage of sodium-ion batteries is the key to making up for the shortcoming of low energy density of sodium-ion batteries. In SIBs, the performance of the positive electrode material directly determines the capacity and output voltage of the battery. Layered transition metal oxide positive electrode material Na x MO2 (M = Fe, Mn, Ni, Co, Cr, Cu, etc. and their combinations) has attracted widespread attention due to its high capacity, simple structure and easy synthesis. This type of material is mainly divided into O3 type and P2 type according to the coordination environment of sodium and the stacking sequence of oxygen. Compared with O3 type, P2 type positive electrode material has a more unobstructed Na + However, at high voltage (>4.2 V), the P2-type cathode material will undergo a phase change from P2 to O2, with a volume change of up to 23% before and after charge and discharge, which will damage its cycle stability. Although the phase change can be avoided by limiting the charging voltage, it also limits the specific capacity of the P2 phase material, which is not conducive to the improvement of the energy density of sodium ion batteries. Recent studies have found that activating anions in the layered cathode material of P2-type sodium ion batteries to achieve O 2-The redox reaction can provide additional charge compensation, thereby greatly improving the specific capacity of the positive electrode material, which is an effective way to improve the energy density of the material. However, TM ion migration is likely to occur while triggering the oxygen valence change, resulting in lattice oxygen loss and irreversible phase change of the matrix material, thereby causing more serious voltage decay and capacity loss. The Chinese patent document with publication number CN 115020676 A discloses a sodium ion battery positive electrode material with stable oxygen valence change and a preparation method thereof, which stabilizes the reversible redox of oxygen and the structure of the positive electrode material by using manganese, nickel and iron concentration gradient metal elements as the core material and the synergistic effect of the shell coating layer structure, but its preparation process is complicated, the process parameters are difficult to control, and the liquid phase preparation process consumes a lot of water resources and also produces a large amount of waste liquid containing heavy metal ions, which is difficult to handle and the cost is too high, which is not conducive to large-scale promotion and application.
[0003] Therefore, how to improve the specific capacity of layered sodium battery positive electrode materials while effectively improving the cycle performance, and at the same time develop a preparation process that is universally applicable to industrial production, is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a sodium ion battery layered oxide positive electrode material based on surface reconstruction and a preparation method thereof, which can improve the interface stability of the sodium battery positive electrode material under high pressure, thereby improving the specific capacity and cycle performance of the material.
[0005] To achieve the above-mentioned object, the present invention provides a sodium ion battery layered oxide positive electrode material based on surface reconstruction, comprising: a positive electrode material body with a layered structure and a reconstruction layer of a disordered rock salt structure on the surface of the positive electrode material body, the whole presenting a disordered rock salt / layered heterogeneous structure; the positive electrode material body is represented by a chemical formula of Na 0.71 Li 0.2 M x Mn 0.8-x O2, measured in molar amount, wherein 0.05≤x≤0.25, M is any one of Al, Fe, and Ni; the reconstruction layer of the disordered rock salt structure is obtained by quenching the cathode material body in a molybdate aqueous solution, and the thickness of the disordered rock salt structure reconstruction layer is 2 to 5 nm; during the quenching process of the cathode material synthesis, the molybdenum ions in the molybdate aqueous solution diffuse into the cathode material body, occupying the octahedral or triangular prism sites in the transition metal layer or the sodium ion layer in the cathode material body structure, and at the same time, the quenching and rapid cooling process causes the atoms on the surface of the cathode material to inherit the disordered structure at the high temperature stage, forming a surface reconstruction layer of the disordered rock salt structure.
[0006] Another object of the present invention is to provide a method for preparing the sodium ion battery layered oxide positive electrode material based on surface reconstruction, which comprises the following steps in sequence:
[0007] (1) Sodium source, lithium source, manganese dioxide and oxide of any one of Al, Fe and Ni are mixed according to the chemical formula Na 0.71 Li 0.2 M x Mn 0.8-x The molar ratio of each element in O2 is weighed, and the sodium source is 3% to 5% in excess of the sodium element, and after mixing, dry ball milling is performed for 5 to 10 hours to obtain a precursor;
[0008] (2) calcining the precursor obtained in step (1) at 300-500° C. for 1-3 h, and then calcining at 900-1000° C. for 8-12 h to obtain a layered oxide positive electrode material body;
[0009] (3) The layered oxide cathode material obtained in step (2) is rapidly quenched and placed in a room temperature molybdate aqueous solution, and then the material is taken out and washed with deionized water and dried in a vacuum to obtain a sodium ion battery layered oxide cathode material based on surface reconstruction.
[0010] Furthermore, in step (1), the sodium source is selected from any one of sodium carbonate, sodium bicarbonate, and sodium acetate, and the lithium source is selected from any one of lithium hydroxide, lithium acetate, and lithium carbonate.
[0011] Furthermore, in the step (2), the heating rate during the calcination process is 1-5°C / min, and the calcination atmosphere is air.
[0012] Furthermore, in step (3), the molybdate is sodium molybdate or potassium molybdate, the concentration of the molybdate aqueous solution is 0.05-0.25 mol / L, the vacuum drying temperature is 110-130° C., and the drying time is 10-12 h.
[0013] Another object of the present invention is that the sodium ion battery layered oxide positive electrode material based on surface reconstruction is used as a sodium ion battery electrode material.
[0014] Compared with the prior art, the present invention has the following advantages:
[0015] 1. The cathode material disclosed in the present invention has a disordered rock salt / layered heterostructure. The electrochemically active disordered rock salt structure surface reconstruction layer generated in situ by quenching fundamentally solves the problem of structural instability under a wide voltage window (2.0-4.5V), prevents the occurrence of surface side reactions and phase changes, slows down the volume effect caused by phase changes during charging and discharging, effectively reduces the harmful effects of electrode-electrolyte interface reactions, inhibits lattice strain and mechanical degradation without sacrificing capacity and kinetic performance, and significantly improves the thermodynamic stability of the cathode material.
[0016] 2. The preparation method of the positive electrode material of the present invention is a simple solid-phase water quenching, the synthesis process is simple, the production efficiency is high, and the raw materials used in the present invention are low-cost, the production process does not require special protection, and is suitable for large-scale production.
[0017] 3. Based on the quenching process, the present invention introduces the molybdenum element with significant corrosion resistance and occupies the octahedral or triangular prism sites in the transition metal layer or the sodium ion layer in the main structure of the positive electrode material. The excellent corrosion resistance and high stability of the molybdenum element in neutral media, acidic media, especially strong oxidizing acid media, and alkaline media, especially alkaline media at high temperatures, are utilized to effectively reduce the occurrence of interfacial side reactions and significantly improve the cycle stability of the positive electrode material under high voltage.
[0018] 4. The sodium ion battery layered positive electrode material provided by the present invention has a discharge capacity retention rate of 92.6%-96.9% after 600 charge and discharge cycles at 1C within a voltage range of 2-4.5V, and a discharge capacity of 191.5mAh / g-196.3mAh / g in a charge and discharge potential window of 2.0-4.5V. It has high specific capacity and high cycle stability, and the preparation method is easy to realize large-scale industrial production, and has high commercial application value for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The X-ray diffraction (XRD) pattern of the sodium ion battery positive electrode material based on surface reconstruction obtained in Example 1;
[0020] Figure 2 This is a scanning electron microscope (SEM) morphology image of the sodium ion battery positive electrode material based on surface reconstruction obtained in Example 2;
[0021] Figure 3 This is a transmission electron microscope (TEM) morphology image of the sodium ion battery positive electrode material based on surface reconstruction obtained in Example 2;
[0022] Figure 4 This is a charge and discharge curve diagram of a half-cell assembled with a sodium ion battery cathode material based on surface reconstruction obtained in Example 2;
[0023] Figure 5 The figure is a comparison chart of the charge and discharge cycle performance of the sodium ion battery positive electrode material obtained in Example 2 and the comparative example. DETAILED DESCRIPTION
[0024] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments. Example 1
[0025] Sodium carbonate, lithium hydroxide, aluminum oxide and manganese dioxide are weighed in corresponding amounts according to the chemical formula stoichiometric molar ratio of Na: Li: Al: Mn = 0.71: 0.2: 0.05: 0.75, and sodium carbonate is weighed on the basis of the molar ratio and an additional 5% excess sodium carbonate is added to compensate for the loss caused by sodium volatilization at high temperature, and then transferred to a ball mill for dry ball milling for 5 hours to obtain a precursor; the precursor is first calcined at 300° C. for 1 hour, and then calcined at 900° C. for 8 hours, the heating rate during the calcination process is 1° C. / min, and the calcination atmosphere is air, so as to obtain the sodium ion battery positive electrode material Na 0.71 Li 0.2 Al 0.05 Mn 0.75 O2, the positive electrode material Na 0.71 Li 0.05 Al 0.05 Mn 0.9 O2 was used as the bulk for rapid quenching in a 0.05 mol / L sodium molybdate aqueous solution at room temperature. The material was then taken out and washed with deionized water and dried in a vacuum oven at a temperature of 110°C for 10 h to obtain a sodium ion battery layered oxide positive electrode material based on surface reconstruction. Figure 1 The XRD diagram of the positive electrode material obtained in this embodiment shows that the product has good crystal morphology and complete crystal form, and the phase composition is a single P2 phase without any impurities. During the quenching process, the molybdenum ions in the molybdate aqueous solution diffuse into the positive electrode material body, occupying the octahedral or triangular prism sites in the transition metal layer or sodium ion layer in the positive electrode material body structure, and the rapid quenching makes the atoms on the surface of the positive electrode material inherit the disordered structure at the high temperature stage, forming a surface reconstruction layer of disordered rock salt structure with a thickness of 2nm, and the obtained positive electrode material has a disordered rock salt / layered heterostructure with a bulk layered structure and a surface disordered rock salt structure, and has a long charge and discharge cycle life in the voltage range of 2 to 4.5V, and the discharge specific capacity retention rate after 600 charge and discharge cycles at 1C is 92.6%, and the discharge specific capacity in the 2.0 to 4.5V charge and discharge potential window is 193.3mAh / g. Example 2
[0026] Sodium bicarbonate, lithium acetate, iron oxide and manganese dioxide are weighed in corresponding amounts according to the chemical formula stoichiometric molar ratio of Na: Li: Fe: Mn = 0.71: 0.2: 0.15: 0.65. Sodium bicarbonate is weighed in molar ratio and 4% excess sodium bicarbonate is added to compensate for the loss caused by sodium volatilization at high temperature. Then, it is transferred to a ball mill for dry ball milling for 8 hours to obtain a precursor; the precursor is first calcined at 400°C for 2 hours, and then calcined at 950°C for 10 hours. The heating rate during the calcination process is 3°C / min, and the calcination atmosphere is air, so as to obtain the sodium ion battery positive electrode material Na0.71 Li 0.2 Fe 0.15 Mn 0.65 O2. The positive electrode material Na 0.71 Li 0.2 Fe 0.15 Mn 0.65 O2 was used as the main body for rapid quenching in a 0.15 mol / L sodium molybdate aqueous solution at room temperature. The material was then taken out and washed with deionized water and dried in a vacuum oven at a temperature of 120°C for 11 hours to obtain a sodium ion battery layered oxide positive electrode material based on surface reconstruction. Figure 2 The scanning electron microscope (SEM) morphology image of the positive electrode material shows that the positive electrode material prepared in this embodiment has a good crystal morphology and a complete crystal form, and the phase composition is a single P2 phase without any impurities. During the quenching process, the molybdenum ions in the molybdate aqueous solution diffuse into the positive electrode material body, occupying the octahedral or triangular prism sites in the transition metal layer or sodium ion layer in the positive electrode material body structure. At the same time, the rapid quenching causes the atoms on the surface of the positive electrode material to inherit the disordered structure at the high temperature stage, forming a surface reconstruction layer of disordered rock salt structure with a thickness of 2.5nm, as shown in the attached Figure 3 As shown in the figure, the prepared positive electrode material has a disordered rock salt / layered heterostructure with a bulk layered structure and a disordered rock salt structure on the surface. It has a long charge and discharge cycle life in the voltage range of 2 to 4.5 V. The discharge capacity retention rate after 600 charge and discharge cycles at 1C is 96.9%. The discharge capacity at 0.1C charge and discharge in the charge and discharge potential window of 2.0 to 4.5 V is 196.3 mAh / g. Figure 4 and attached Figure 5 shown. Example 3
[0027] Sodium acetate, lithium carbonate, nickel oxide and manganese dioxide are weighed in corresponding amounts according to the chemical formula stoichiometric molar ratio of Na: Li: Ni: Mn = 0.71: 0.2: 0.25: 0.55, and sodium acetate is weighed on the basis of the molar ratio and an additional 3% excess sodium acetate is added to compensate for the loss caused by sodium volatilization at high temperature, and then transferred to a ball mill for dry ball milling for 10 hours to obtain a precursor; the precursor is first calcined at 500° C. for 3 hours, and then calcined at 1000° C. for 12 hours, the heating rate during the calcination process is 5° C. / min, and the calcination atmosphere is air, so as to obtain the sodium ion battery positive electrode material Na 0.71 Li 0.2 Ni 0.25 Mn 0.55 O2. The positive electrode material Na 0.71 Li 0.2 Ni 0.25 Mn 0.55O2 was used as the main body for rapid quenching in a 0.25 mol / L potassium molybdate aqueous solution at room temperature, and then the material was taken out and washed with deionized water and dried in a vacuum oven at a vacuum oven temperature of 130°C for 12 hours to obtain a sodium ion battery layered oxide positive electrode material based on surface reconstruction. The positive electrode material prepared in this embodiment has a good crystal morphology and a complete crystal form, and the phase composition is a single P2 phase without any impurity phase. During the quenching process, the molybdenum ions in the molybdate aqueous solution diffuse into the cathode material body, occupying the octahedral or triangular prism sites in the transition metal layer or the sodium ion layer in the cathode material body structure. At the same time, rapid quenching causes the atoms on the surface of the cathode material to inherit the disordered structure at the high temperature stage, forming a surface reconstruction layer of a disordered rock salt structure with a thickness of 5 nm. The prepared cathode material has a disordered rock salt / layered heterostructure of a bulk layered structure and a surface disordered rock salt structure. It has a long charge and discharge cycle life in the voltage range of 2 to 4.5 V. The discharge specific capacity retention rate after 600 charge and discharge cycles at 1C is 95.4%, and the discharge specific capacity in the charge and discharge potential window of 2.0 to 4.5 V is 191.5 mAh / g. Comparative Example
[0028] Sodium bicarbonate, lithium acetate, iron oxide and manganese dioxide are weighed in corresponding amounts according to the chemical formula stoichiometric molar ratio of Na: Li: Fe: Mn = 0.71: 0.2: 0.15: 0.65. Sodium bicarbonate is weighed in molar ratio and 4% excess sodium bicarbonate is added to compensate for the loss caused by sodium volatilization at high temperature. Then, it is transferred to a ball mill for dry ball milling for 8 hours to obtain a precursor; the precursor is first calcined at 400°C for 2 hours, and then calcined at 950°C for 10 hours. The heating rate during the calcination process is 3°C / min, and the calcination atmosphere is air, so as to obtain the sodium ion battery positive electrode material Na 0.71 Li 0.2 Fe 0.15 Mn 0.65 The positive electrode material prepared in this comparative example has good crystal morphology and complete crystal form, and the phase composition is a single P2 phase without any impurity phase. The discharge capacity retention rate after 600 charge and discharge cycles at 1C is 71.6% within the voltage range of 2 to 4.5V, and the discharge capacity within the charge and discharge potential window of 2.0 to 4.5V is 174.8mAh / g.
[0029] Compared with Example 2, the only difference is that the comparative example does not undergo quenching operation, and other operations and parameters are the same as Example 2. The discharge capacity retention rate of the sodium ion battery positive electrode material after 1C charge and discharge cycles of 600 times is 71.6%, compared with the discharge capacity retention rate of 96.9% of the sodium ion battery positive electrode material after quenching operation in Example 2 after 600 cycles, the long-term cycle stability of the comparative example material is significantly reduced, which shows that the quenching operation is crucial to improving ion diffusion kinetics and long-term stability. The preparation method disclosed in the present invention adopts a quenching process method of a molybdate aqueous solution after solid-phase sintering, and utilizes the rapid cooling effect of water quenching to make the atoms on the surface of the positive electrode material inherit the disordered structure at the high temperature stage, forming a surface reconstruction layer with a disordered rock salt structure. At the same time, the molybdenum ions in the molybdate aqueous solution diffuse into the positive electrode material body, occupy the octahedral or triangular prism sites in the transition metal layer or the sodium ion layer in the positive electrode material body structure, and in-situ construct a reconstruction layer with electrochemical activity on the interface of the positive electrode material. The process is simple and efficient, and effectively improves the interface stability of the sodium positive electrode material under high pressure, thereby improving the energy density and long cycle performance of the material.
Claims
1. A sodium ion battery layered oxide positive electrode material based on surface reconstruction, characterized in that: The positive electrode material comprises: a positive electrode material body with a layered structure and a reconstructed layer of disordered rock salt structure on the surface of the body, and the whole is a disordered rock salt / layered heterogeneous structure; the positive electrode material body is represented by a chemical formula of Na 0.71 Li 0.2 M x Mn 0.8-x O2, in molar amount, wherein 0.05≤x≤0.25, M is any one of Al, Fe, and Ni; the disordered rock salt structure reconstruction layer is obtained by quenching the cathode material body in a molybdate aqueous solution, and the thickness of the disordered rock salt structure reconstruction layer is 2 to 5 nm; During the quenching process of the positive electrode material synthesis, the molybdenum ions in the molybdate aqueous solution diffuse into the positive electrode material body, occupying the octahedral or triangular prism sites in the transition metal layer or the sodium ion layer in the positive electrode material body structure, and at the same time, the quenching and rapid cooling process causes the atoms on the surface of the positive electrode material to inherit the disordered structure at the high temperature stage, forming a surface reconstruction layer of disordered rock salt structure; The method for preparing the sodium ion battery layered oxide positive electrode material based on surface reconstruction is prepared by the following steps: (1) Sodium source, lithium source, manganese dioxide and oxide of any one of Al, Fe and Ni are mixed according to the chemical formula Na 0.71 Li 0.2 M x Mn 0.8-x The molar ratio of each element in O2 is weighed, and the sodium source is 3% to 5% excess based on the sodium element. After mixing, dry ball milling is performed for 5 to 10 hours to obtain a precursor; (2) calcining the precursor obtained in step (1) at 300-500° C. for 1-3 h, and then calcining at 900-1000° C. for 8-12 h to obtain a layered oxide positive electrode material body; (3) The layered oxide cathode material obtained in step (2) is rapidly quenched and placed in a room temperature molybdate aqueous solution, and then the material is taken out, washed with deionized water, and then vacuum dried to obtain a sodium ion battery layered oxide cathode material based on surface reconstruction.
2. The sodium ion battery layered oxide positive electrode material based on surface reconstruction according to claim 1, characterized in that: In the step (1), the sodium source is selected from any one of sodium carbonate, sodium bicarbonate and sodium acetate, and the lithium source is selected from any one of lithium hydroxide, lithium acetate and lithium carbonate.
3. The sodium ion battery layered oxide positive electrode material based on surface reconstruction according to claim 1, characterized in that: The heating rate during the calcination process in step (2) is 1-5°C / min, and the calcination atmosphere is air.
4. The sodium ion battery layered oxide positive electrode material based on surface reconstruction according to claim 1, characterized in that: In the step (3), the molybdate is sodium molybdate or potassium molybdate, the concentration of the molybdate aqueous solution is 0.05-0.25 mol / L, the vacuum oven drying temperature is 110-130° C., and the drying time is 10-12 h.
5. An application of a sodium ion battery layered oxide positive electrode material based on surface reconstruction as claimed in claim 1, characterized in that: It is used as an electrode material for sodium-ion batteries.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material with stable oxygen variable valence and preparation method of sodium-ion battery positive electrode material
CN115020676A
High-performance sodium ion battery layered oxide electrode material
CN115377409A
P2-type manganese-based sodium ion positive electrode layered material based on co-doping of lithium and nickel as well as preparation method and application of P2-type manganese-based sodium ion positive electrode layered material
CN117613260A
Sodium-ion battery positive electrode material and preparation method thereof
CN118213514A